Comparison of incisive canal remodeling and root resorption in extraction vs. non-extraction fixed orthodontic retraction: a CBCT study - Al-Rokhami, Remsh Khaled; Gao, Deguo; Dang, Xiaobao; Jiang, Ruiqing; Zhang, Guangfeng; Sakran, Karim Ahmed (Frontiers in Physiology, 2025)
BackgroundThis study evaluated three-dimensional changes in incisive canal (IC) morphology, root–IC proximity, and apical root resorption following fixed orthodontic retraction, comparing extraction and non-extraction protocols.MethodsCBCT scans of 86 patients (172 maxillary central incisors; mean age 22.3 ± 5.7 years) were analyzed before (T1) and immediately after treatment (T2). Participants were assigned to extraction (n = 42) or non-extraction (n = 44) groups. Linear measurements (IC width, cortical bone width, root–IC distance, U1 length/width, IC height) were recorded at three vertical levels (H1–H3). IC and U1 volumes and surface areas were quantified using standardized 3D segmentation. Continuous group comparisons were performed using patient-averaged data, whereas incisor-level categorical outcomes were analyzed using cluster-adjusted statistical models. Root–IC proximity patterns were evaluated using Generalized Estimating Equations (GEE), and apical root resorption and volumetric changes were assessed using Linear Mixed Models (LMM). Predictors of root–IC contact/invasion and predictors of root–IC distance reduction were examined using multivariable GEE and LMM, respectively. Multiplicity was controlled using Holm–Bonferroni correction.ResultsIC width and cortical bone width decreased at several levels in both groups, more prominently in extraction cases (P < 0.05). Root–IC distance decreased in all patients, with an adjusted overall mean reduction of 1.33 mm (95% CI, 1.28–1.37). LMM showed no independent effect of extraction status on root–IC distance change (B = 0.08, P = 0.079). Each millimeter of U1 retraction produced an additional 0.40 mm reduction in root–IC distance (95% CI, 0.37–0.43; P < 0.001). GEE demonstrated that each millimeter of U1 movement increased the odds of root–IC contact or invasion by 1.76-fold (95% CI, 1.21–2.56; adjusted P = 0.030). Apical root resorption was significantly higher in teeth showing canal contact or invasion, with an average 0.38 mm greater shortening compared with separated roots (95% CI, 0.08–0.69).ConclusionChanges in root–IC proximity during orthodontic retraction are driven primarily by the magnitude of tooth movement, not extraction status. Greater retraction increases both canal approximation and the likelihood of contact/invasion, which in turn intensifies apical root resorption. Pre-treatment CBCT assessment of IC morphology and careful force and torque control are essential to minimize biomechanical overload and reduce iatrogenic risk during orthodontic retraction.